Does Laminar Airflow in the Operating Room During Total Knee Arthroplasty Lead to More Perioperative Hypothermia Compared to Conventional Airflow?: A Randomized Clinical Trial - Dagli, Recai; Çelik, Fatma; Yetiş, Mehmet; Ünveren, Zafer (My University, 2024)
Purpose: Spinal anesthesia disrupts the body's thermoregulatory response, often leading to undesired perioperative hypothermia (<36ºC), especially in major surgeries such as total knee arthroplasty (TKA). In operating rooms with a laminar airflow system (LAS-OR), the airflow direction differs from conventional airflow systems (CAS-OR) by being directed directly onto the surgical table. The aim of this study is to answer the question, \"Does laminar airflow in the operating room during total knee arthroplasty lead to more perioperative hypothermia compared to conventional airflow?\" Materials and Methods: This study is a prospective, randomized controlled trial. Patients were divided into two groups, Group L (operated in LAS-OR) (n=110) and Group C (operated in CAS-OR) (n=110), using simple randomization with sealed envelope method. The frequencies of perioperative hypothermia (IPH) were compared between the groups. (Clinical trial registration number/date: IRCT20180324039145N4 / 2018.10.31) Results: In Group L, data from 94 patients and in Group C, data from 89 patients were evaluated. During TKA, the frequency of perioperative hypothermia (IPH) was 56.8% (104 out of 183 patients), with no statistical difference found between Group L and Group C (62.8% (59 out of 94 patients) vs. 50.6% (45 out of 89 patients), p=0.096). At the 105th minute, Group L experienced a temperature decrease of 0.76 (±0.47) ºC (95% CI: 0.61 to 0.91), whereas Group C had a temperature decrease of 0.74 (±0.51) ºC (95% CI: 0.58 to 0.90), with no significant difference observed (p=0.823). Conclusion: There is no difference in the frequency of perioperative hypothermia (IPH) between operating rooms with laminar and conventional airflow during total knee arthroplasty under spinal anesthesia.
Keywords: Patient safety; spinal anaesthesia; knee arthroplasty; intraoperative hypothermia; laminar airflow